2018
DOI: 10.1007/s13197-018-3086-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of lentil, pea, and faba bean hulls in Turkish noodle production

Abstract: Turkish noodles (erişte) were substituted with green lentil (), red lentil (), faba bean (), and pea () hulls at the level of 2.5, 5, and 10% and the effects of the substitution on proximate composition, mineral composition, colour, cooking properties, thiamine and riboflavin contents, texture and sensory properties of the noodles were investigated. Crude ash, dietary fibre, Ca and Mg contents of the noodles significantly increased with pulse hull substitution regardless of the hull type compared to control. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
3
24
1
Order By: Relevance
“…In accordance with our results, Kaya et al [ 33 ] reported a reduction of protein content in Turkish noodles enriched with pea and faba bean hull, as the level of hull increased.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with our results, Kaya et al [ 33 ] reported a reduction of protein content in Turkish noodles enriched with pea and faba bean hull, as the level of hull increased.…”
Section: Resultssupporting
confidence: 93%
“…Legume hulls can be used as a source of fibre in different food products, such as Turkish noodles and meat products [ 33 , 34 ]. Noodles substituted with different levels (2.5, 5, and 10%) of hull obtained from different legumes (green lentil, red lentil, faba bean, and pea) showed a significantly higher total dietary fibre content than control [ 33 ]. In particular, the addition of legume hull increased the fibre content of noodles up to 8.3% at the maximum level of substitution (10%) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to enhance the quality or nutritional value of pasta, other ingredients, such as milk, eggs, vegetables, etc. are added [3]. Nonetheless, the essential ingredient is appropriate flour that ensures good quality delivered to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Turkish noodles can be enriched with various protein sources, dietary fiber and micronutrients to improve their nutritional properties. In the literature, some cereal flours (Aydin and Gocmen, 2011), pseudo cereals (Bilgiçli, 2009;Bilgiçli, 2014), legume flours (Demir et al, 2010;Bilgiçli et al, 2011;Bilgiçli, 2013), cereal and legume brans (Ertaş, 2014;Yılmaz Tuncel et al, 2017;Kaya et al, 2018), wheat germ and β glucan (Aktaş et al, 2015), some fruit seed flour (Koca et al, 2018), chia flour (Levent, 2017), dairy by products (Aktaş andTürker, 2015), flaxseed (Yüksel et al, 2018), apple fiber (Yuksel and Gurbuz, 2019) have been used for enrichment of the Turkish noodles.…”
Section: Introductionmentioning
confidence: 99%